UPAYA PARTISIPATIF DALAM PENCEGAHAN KEKERASAN SEKSUAL MELALUI UNIT KEGIATAN MAHASISWA CAKRA HARMONI DI UNIVERSITAS NEGERI SURABAYA - Khoirunnisa, Aida; Wijaya, Rahmanu (Universitas Negeri Surabaya (Unesa), 2025)
Sexual violence in higher education is a serious issue that affects students' sense of safety, comfort, and their right to a dignified education. Universitas Negeri Surabaya (UNESA) responded to this issue by establishing the Task Force for the Prevention and Handling of Sexual Violence (Satgas PPKPT) and supporting student involvement through the student organization Cakra Harmoni. This organization serves as a strategic partner in preventive efforts through educational approaches, campaigns, and training programs. This study aims to describe student participation in preventing sexual violence through Cakra Harmoni. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation involving seven informants, including UKM administrators, academic advisors, and representatives from the Satgas PPKPT and the Sub-directorate of PPKIS UNESA. The findings show that students are actively involved in planning, implementing, and evaluating programs such as Anti-Violence Week, Valentine Talks, social media campaigns, and peer counselor training. Despite challenges like limited resources and divided focus among members, Cakra Harmoni plays a crucial role in fostering a campus culture that is responsive to sexual violence. Keywords: Student Participation, Sexual Violence Prevention, UKM Cakra Harmoni, Safe Campus, UNESA